Cellulose produced by Gluconacetobacter xylinus strains ATCC 53524 and ATCC 23768: Pellicle formation, post-synthesis aggregation and fiber density. (20th November 2015) - Lee, Christopher M.; Gu, Jin; Kafle, Kabindra; Catchmark, Jeffrey; Kim, Seong H.
Highlights: Pellicles of crystalline cellulose were synthesized by G. xylinus strains ACCC 53524 and ATCC 23769 for 1 day and 7 days. The changes in cellulose microfibril aggregation were monitored using sum frequency generation (SFG) vibration spectroscopy and scanning electron microscopy (SEM). SEM showed that newly synthesized cellulose microfibrils are deposited at the top of the pellicle. SEM and SFM showed that the aggregation and packing of cellulose microfibrils was greatest at the top of the pellicle after 7 days culture compared to cellulose microfibrils at the bottom of 7 day pellicles. Abstract: The pellicle formation, crystallinity, and bundling of cellulose microfibrils produced by bacterium Gluconacetobacter xylinus were studied. Cellulose pellicles were produced by two strains (ATCC 53524 and ATCC 23769) for 1 and 7 days; pellicles were analyzed with scanning electron microscopy (SEM), X-ray diffraction (XRD), vibrational sum-frequency-generation (SFG) spectroscopy, and attenuated total reflectance infrared (ATR-IR) spectroscopy. The bacterial cell population was higher at the surface exposed to air, indicating that the newly synthesized cellulose is deposited at the top of the pellicle. XRD, ATR-IR, and SFG analyses found no significant changes in the cellulose crystallinity, crystal size or polymorphic distribution with the culture time. However, SEM and SFG analyses revealed cellulose macrofibrils produced for 7 days had a higher packing density at the top of the pellicle, compared to the bottom. These findings suggest that the physical properties of cellulose microfibrils are different locally within the bacterial pellicles.